Interdisiplin ilmu pemerintahan Pancasila : sinkron-integratif kommitmen politik Orde Baru - Ridwan, Ahmad Fauzie (Yayasan Karya Dharma, Institut Ilmu Pemerintahan, 1979)
On P4, the guide for living by the precepts of Pancasila, the Indonesian state philosophy with special references to social, religious, and community development.